An energy-efficient service-oriented energy supplying system and control for multi-machine in the production line. (15th March 2021) - Li, Lei; Huang, Haihong; Zou, Xiang; Zhao, Fu; Li, Guishan; Liu, Zhifeng
Highlights: The system centralizes energy conversion units with different output power. Building a response and request mechanism for energy service supplying. Developing a task-based agent design to configure the production line for efficiency. The system owns better energy-saving effect than the commonly used servo system. Abstract: Energy efficiency is of great significance in manufacturing to lower emissions and costs. Focusing on the production line featured with multi-machine and multi-task, a novel service-oriented energy supplying system where the energy supplying is deemed as a service is developed to improve efficiency. The service-oriented energy supplying system centralizes energy conversion units with different levels of output power as service agents to respond to the energy requirements of individual machines, and each machine requests a service that can match the power demand of the corresponding task. The architecture and mathematical model of all entities in the system were established to reveal the working process. The task-based agent design for the production line with different tasks was further developed to configure the system and construct the response mechanism to ensure the efficiency of energy conversion units. To validate the effectiveness, the system was applied on a production line that consists of four processes to form a clutch shell. Results show that the proposed system owns better energy-saving effects than that of the servo system with the performance of high energy efficiency, i.e., 6.42% of the energy consumption can be saved during a working cycle. The reason for energy saving was analyzed and how to further improve the efficiency of the system from the perspective of agent design was discussed. The proposed system assists in designing and operating multi-machine in a production line with similar tasks to be completed for higher energy efficiency.